(untitled) (International Conference on Computers in Education, 2016)
Mobile technique and device development have become mature. Online community and application of social networking facilitate our connection and communication with other people. However, the design of social networking supporting learning activity still remains many gaps. The aim of this study is to demonstrate the relational design oriented seamless framework and the seamless learning environment architecture. Currently, a platform named cocoing.info is under construction based on the proposed frameworks. In the future, the users’ behavior on the platform will be collected and analyzed.